HealthBread: Wholegrain and high fibre breads with optimised textural quality. (November 2017) - Noort, Martijn W.J.; Mattila, Outi; Katina, Kati; van der Kamp, Jan Willem
Abstract: The aim of this study was to develop healthy wholegrain and high fibre bread products with sensory attributes similar to white bread by applying a combination of technological steps: the use in addition to flour of a specific wheat fraction with high levels of fibre and micronutrients, bioprocessing of this fraction with enzymes and yeast (pre-fermentation) and by the optimisation of dough formulation. The pre-fermentation can be modelled and optimised to improve the bioavailability of nutrients without major fibre degradation, including a +200% increased soluble free ferulic acid level, and to improve its technical functionality in the dough mixing process. It also had a positive effect on the textural quality of bread. An experimental design approach was used to achieve optimal dough formulation based on the use of pre-fermentation, vital gluten and enzymes in the dough. Commercial bread products with optimised sensory product quality were developed with high nutritional quality - being high in fibre, and a source of important micronutrients such as iron, magnesium, zinc and folate. The study shows that it is possible to develop nutritionally improved bread products with textural quality similar to white bread. Graphical abstract: Highlights: Pre-fermentation can improve the nutritional and technological functionality of bran. In combination with optimised formulation good wholegrain bread quality was obtained. Bread volume and textural properties were close to those of white bread. Reduced staling was found, mechanism is not yet clear. Industrial application of results led to attractive wholegrain products.